Behavior of API 5L X56 submarine pipes under transverse impact. (15th June 2020) - Gao, Xudong; Shao, Yongbo; Xie, Liyuan; Yang, Dongping
Abstract: The performance of API 5L X56 submarine pipes subjected to transverse impact is investigated through both drop weight impact tests and finite element simulations. To study the improvement of resistance to transverse impact for pipe-in-pipe specimens, corresponding single-layer pipe specimens under impacting load were also tested for comparison. From the experimental tests, the failure mode, the impact force-time history curve, the displacement-time history curve, the strain-time history curve and the impact force - displacement curve of all specimens were obtained. The pipe-in-pipe specimens are found to have superior performance to resist impacting loading compared to single-layer specimens because smaller global bending deformation and local indentation were observed in them. In addition, the cross-section deformation rate, R, was proposed, and the local indentation length of the specimen was divided into three zones based on experimental observation and numerical simulation. A comprehensive comparison of the length and the depth of local indentation in the pipe-in-pipe specimens shows that the local indentation decreases and the impact resistance increases due to the presence of the inner tube. Finally, the post-peak mean force ( P m ) and the energy absorption capacity (EAC) were used to evaluate the energy dissipation mechanism of different specimens. The results also indicate that the pipe-in-pipe specimens have better energy absorption performance. Highlights: Impact tests on 5 pipe-in-pipe specimens and 3 single-layer pipe specimens were conducted. Failure mode, time history curves of impact force, displacement and strain, and impact force-displacement curve are obtained. Difference of impact resistance between pipe-in-pipe and single-layer pipe specimens is compared and analyzed. Post-peak mean force and energy absorption capacity are used to evaluate energy dissipation mechanism of pipes.